Analisis Hasil Pemeriksaan Sistem Pengendalian Internal atas Pembayaran Hutang Usaha, Penerimaan Dan Pengeluaran Barang Pada PT Niaga Multi Indo - Yenny Elfiza Abbas (Cakrawala Akuntansi & Manajemen, 2022)
Internal Control is a process imposed by the management (board of directors) and overall management, designed to give a belief in the achievement of corporate objective that are generally divided into three categoris. Effectiveness and efficiency of company operations, reliable financial reporting, Compliance to procedures and regulations applied. In line with the development of the company, it will arise problems caused by the widespread scope and opertional activities of the company. This study aims to determine whether the “Internal Control System Against Procedure of Receipt and Spending on PT. Niaga Multi Indo Commerce”. The results of the analysis from audit and discussion in the research at PT. Niaga Multi Indo Commerce is the existence of a function or occupation positions performed by the accounting department that doubles as function of receipt of goods, the function of storage of goods (warehouse) due to the lack of separation of functions clearly in this section. Errors in the recording of debt, inventories, receipts and disbursement of goods, as a result of many request made orally, without using the form tothe parts concerned.